Development programs, household income and economic vulnerability: a study among low-income households in Peninsular Malaysia - Al Mamun, Abdullah; Ibrahim, Mohd Asrul Hery; Muniady, Rajennd; Ismail, Mohammad; Che Nawi, Noorshella; Md Nasir, Noorul Azwin (Emerald Publishing Limited, 2018)
Purpose – The purpose of this paper is to improve the socio-economic condition of low-income households in Malaysia, many products and services are available, including access to working capital and enterprise development training programs. This study examined the impact of access to working capital and micro-enterprise development training programs on household income and economic vulnerability among participants of development initiatives in the eKasih (national poverty data bank) in Peninsular Malaysia. Design/methodology/approach - Adopting a cross-sectional design, the authors collected data randomly from the selected 300 micro-entrepreneurs from the list of development organizations available in the eKasih (national poverty data bank) located in four states of Peninsular Malaysia. Quantitative data were collected through structured interviews with the respondents from October to November 2017. Findings – Both the length of participation and total amount of economic loan were found to increase the household income. However, there was no positive and significant impact of total number of training hours on household income. Interestingly, length of participation was found to reduce the level of economic vulnerability, except total amount of economic loan, and total number of training hours. Originality/value – Despite the overwhelming empirical evidence, the findings indicated that the impact of enterprise development training programs was inconclusive. The effect of total amount of loan on economic vulnerability was also inconclusive. Hence, both policy makers and development organizations should understand how their programs benefit the poor households that can be improved through new implementation strategies.